Isolated Thyroid Cartilage Fracture Caused by Neck Hyperextension During Motor Vehicle Accident with Atypical Neck Pain (Case Report) - Eke, Salih Murat; Alan, Ömer; Sonkaya, Murat (The Bulletin of Legal Medicine, 2022)
Traffic accidents are one of the most important traumas that cause injuries to the laryngotracheal skeletal system. These injuries can vary from simple fracture of the thyroid cartilage to cartilage slips, cartilage defects, intralaryngeal tears or laryngotracheal separation. A forty-four-yearold male, hit the another vehicle from behind with his car and was injured when the airbag hit his chest wall. In the case who described atypical neck pain, radiological fracture was detected in the right upper horn of the thyroid cartilage due to hyperextension of the neck. Our case warns us that the atypical complaints are due to an important medical injury such as thyroid cartilage fracture. In addition the formation of the fracture as a result of indirect trauma and hyperextension of the neck was found interesting because it is less common than fractures due to hyperflexion of the neck described in the literature and presented with radiological findings.